Association of Angiotensin Converting Enzyme (insertion\deletion) and Angiotensin II Type 1 Receptor (A1166C) gene polymorphisms with diabetic nephropathy in Iraqi type 2 diabetic patients - Ansam Abdulameer Yahya; Dheyaa Jabbar; Nassar Abdalaema Abdalhadi (College of Pharmacy University of Baghdad, 2024)
Renin-angiotensin-aldosterone system abnormalities are the most prevalent cause of renal hemodynamic abnormalities, and candidate genes in this system are involved in the etiology of diabetic nephropathy (DN). A polymorphism in the angiotensin converting enzyme (ACE) gene I(insertion)\D(deletion) has been correlated to plasma ACE levels. Furthermore, the Angiotensin II Type 1 Receptor AGT1R (A1166C) expression pattern is highly related to nephropathy. The objectives of this study involved evaluating the frequency of the ACE (I/D) and AGT1R (A1166C) gene polymorphisms and investigating the association of these polymorphism with the development of DN in Iraqi patients with Type 2 diabetes mellitus (T2DM) and evaluating the levels of several urinary and serum markers in relation to studied polymorphisms. This is a cross-sectional study that included 161 T2DM patients whom were divided into two groups: T2DM with DN(included 98 patients) and normalbuminuric T2DM (included 63 patients). ACE gene polymorphism analysis revealed that the D allele was far more prevalent in DN patients compared to normalbuminuric patients (60.2% vs. 50.8%), while the I allele frequency was 39.8% in DN and 49.2% in normoalbuminuric patients. In addition, DN patients carrying the DD genotype had higher serum kidney injury molecule 1 (KIM1), serum cystatin C (CysC), and HbA1C and lower glomerular filtration rate (GFR) compared to ID+II genotypes. For AGT1R (A1166C), both DN and normalbuminuric patients had a comparable high prevalence of the AA genotype, followed by the AC genotype, while the CC genotype had been seen only in 3 patients. In conclusion, among the studied T2DM patients, individuals with DD genotype had higher frequency of DN and had 2-fold risk for DN compared to II genotype which had the lowest risk for DN. Also the current study shows that the A1166C polymorphisms of AGT1R distribution frequency were similar for both study groups with higher frequency for A allele compared to C allele and not associated with risk of DN in Iraqi T2DM Keywords: Angiotensin Converting Enzyme (I\D) gene polymorphism, Angiotensin II Type 1 Receptor (A166C) gene polymorphisms, Cystatin C, Diabetic nephropathy, Kidney injury molecule1.